THE EFFECT OF ULTRASOUND AND MICROWAVE DIATHERMY IN SHOULDER PERIARTHRITIS - Volkan Arıkan; Cahit Kaçar; Erdal Gilgil; Sevgi Urhan; Tiraje Tuncer; Bülent Bütün; Aker Akyokuş (Archives of Rheumatology, 2004)
Physical agents are widely and reliably used in conservative management of shoulder periarthritis (SP). The aim of this study was to compare the effectiveness of mostly used modalities such as ultrasound (US) and microwave diathermy (MWD) in the management of SP. Fifty-six patients were recruited in this study and separated randomly in two groups as US or MWD therapy. The efficacy of US and MWD was evaluated by clinical findings, level of functional limitation and ultrasonographic findings. Pain at night, pain at daytime (VAS) and range of motion improved in both of the treatment groups, though more significantly in US group. We found that both US and MWD, and therapeutic exercise led to both clinical and ultrasonographic improvement.